2003
DOI: 10.1104/pp.103.029728
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Carbon Limitation Induces Transcripts Encoding Components of the CO2-Concentrating Mechanism in Synechococcus sp. PCC7942 through a Redox-Independent Pathway

Abstract: The cyanobacterial CO 2-concentrating mechanism (CCM) allows photosynthesis to proceed in CO 2-limited aquatic environments , and its activity is modulated in response to inorganic carbon (Ci) availability. Real-time reverse transcriptase-PCR analysis was used to examine the transcriptional regulation of more than 30 CCM-related genes in Synechococcus sp. strain PCC7942 with an emphasis on genes encoding high-affinity Ci transporters and carboxysome-associated proteins. This approach was also used to test hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
111
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 52 publications
20
111
2
Order By: Relevance
“…Genes coding for proteins involved in the active uptake of C i (bicarbonate and/or CO 2 ) as part of the CCM showed the highest increase in transcript levels 6 h after the LC shift, as was found previously by reverse transcription-PCR and northern-blot hybridization in Synechococcus species (Woodger et al, 2003(Woodger et al, , 2007 and in Synechocystis 6803 (Wang et al, 2004;Eisenhut et al, 2007). The strongest responses are found for the bicarbonate-specific ATP-binding cassette transporter BCT1 and the symporter SbtA (Table II).…”
Section: General Changes In the Transcriptome Of Synechococcus 7942 Dsupporting
confidence: 80%
See 3 more Smart Citations
“…Genes coding for proteins involved in the active uptake of C i (bicarbonate and/or CO 2 ) as part of the CCM showed the highest increase in transcript levels 6 h after the LC shift, as was found previously by reverse transcription-PCR and northern-blot hybridization in Synechococcus species (Woodger et al, 2003(Woodger et al, , 2007 and in Synechocystis 6803 (Wang et al, 2004;Eisenhut et al, 2007). The strongest responses are found for the bicarbonate-specific ATP-binding cassette transporter BCT1 and the symporter SbtA (Table II).…”
Section: General Changes In the Transcriptome Of Synechococcus 7942 Dsupporting
confidence: 80%
“…Furthermore, the transcript levels of the pyruvate kinase-encoding gene orf0098 and the gene orf2384, which encodes a component of the pyruvate dehydrogenase, are also approximately 3.5-fold increased after the long-term LC shift. However, the gene for PEP carboxylase (ppc; orf2252) did not change expression under LC conditions (Table I), as reported previously (Woodger et al, 2003). It may further be hypothesized that the glyceraldehyde-3-phosphate dehydrogenase isoform encoded by orf1939 is implicated in the glycolytic pathway rather than in the Calvin-Benson cycle.…”
Section: Correlation Of Metabolic With Transcriptomic Changes In Wildsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition to general photosystem proteins, proteomic evidence of the pigment differences between Prochlorococcus and Synechococcus were observed with chlorophyll and carotenoid synthesis proteins detected for Prochlorococcus and phycobilisome proteins detected for Synechococcus. Carboxysome proteins, which are induced by inorganic carbon limitation and are thought to be signaled by high light (McKay et al, 1993;Woodger et al, 2003) were also observed, with peptides for the Synechococcus orthologs appearing more frequently. The carboxysome allows cyanobacteria to overcome inorganic carbon limitation by concentrating CO 2 for its conversion to organic carbon by the enzyme ribulose 1, 5 bisphosphate carboxylase/oxygenase (RuBis-CO), which was also detected.…”
Section: Abundant Cyanobacterial Proteinsmentioning
confidence: 99%